PENGARUH LEVERAGE KEUANGAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Ashari, Muhammad Hajar; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2017)
Based on data from BPS in 2017, the company's debt in the hotel, restaurant and tourism sector has the highest debt rate compared to other sectors. This attracts writers to find out whether the high debt to tourism companies has a significant effect on the profitability of the company.The main objective this study is to examine the effect of debt to assets ratio (DAR), debt to equity ratio (DER), degree of financial leverage (DFL), long debt to equity ratio (LDER), and time interest earned ratio (TIER) on return on equity (ROE) simultaneously and partially in torism companies. Multiple linier regression analysis is used as a data analysis tool with return on equity (ROE) as the dependent variable.This study uses secondary data derived from the financial statements of tourism companies listed on IDX period 2011-2015. Purposive sampling is used as a sampling method and obtained 10 companies from 23 companies listed on IDX.The result of this research shows that DAR, DER, DFL, LDER, and TIER have simultaneous and significantly influence toward ROE. Partially, DAR has positive and significant effect to ROE, while DER has negative and not significant effect to ROE. The DFL variable has a positive and significant effect on ROE, while LDER has a negative and significant effect on ROE. The TIER variable has a negative and insignificant effect on ROE at the 5% significance level.